Chemical Constituents from the Leaves and Stems of Piper ornatum N.E.Br (Piperaceae) and their Antioxidant Activity - Nik Nur Asyiqin Nik Mohammed Ainul Azman (Tanjung Malim, 2023)
Chemical Constituents from the Leaves and Stems of Piper ornatum N.E.Br (Piperaceae) and their Antioxidant Activity by Nik Nur Asyiqin Nik Mohammed Ainul Azman